Empirical Investigation of Monga Combat Strategies in Northwest Bangladesh - Siddiki, Ubaydur Rahaman; Ansari, Mohammad Nayeem Aziz (The Jahangirnagar Review, 2024)
Monga, colloquially referred to as a 'famine-like situation,' is a recurrent challenge in specific areas within the Rangpur division of northwest Bangladesh. The impact of Monga is particularly pronounced among agriculturally dependent families and low-income individuals in this region. Its adverse effects extend beyond local livelihoods, detrimentally influencing the socio-economic landscape of the Monga-affected area, which, in turn, poses a vulnerability to the broader national economy of Bangladesh. To ensure the sustainable progress of the country, it becomes imperative to implement diverse strategies aimed at ameliorating the conditions in the northwest regions impacted by Monga. Consequently, both governmental bodies and non-governmental organizations (NGOs) have initiated an array of intervention programs with short-term and long-term implications. These initiatives encompass social safety nets, agricultural diversification, and microcredit programs, supplementing the ongoing efforts by focusing on households vulnerable to Monga in northwest Bangladesh. Considering these premises, this study scrutinizes the efficacy of the undertaken measures. Employing various qualitative methodologies alongside document analysis, this research offers an empirical assessment conducted in a selected village within Domar Upazila in Nilphamari District. This region witnesses substantial engagement from governmental and non-governmental entities striving to combat Monga. The findings underscore how diverse actors' interventions have collectively mitigated the severity of Monga's impact on the villages, including its recurring nature. Among the interventions, the standout program is agricultural diversification incorporating Short Durational Rice (SDR) varieties and multiple cropping, coupled with short-to-long-term social programs like safety nets and community-driven efforts such as the Dhan Bank. While the study unveils the influence of macroeconomic policies on micro-level political economy choices that have reshaped the coping strategies of Monga-affected individuals, it also identifies critical gaps in program coverage, particularly in safety net initiatives. It is evident that only a limited number of existing programs are explicitly designed as risk-reduction measures targeted at addressing the Monga situation. Moreover, the implementation of some short-term solutions occasionally encounters hindrances, often due to internal and external factors. A case in point is the PRIME program, which was discontinued before its scheduled completion in 2011 (PKSF, 2012). Additionally, the prevailing policies and strategies aimed at tackling the Monga situation in Northern Bangladesh predominantly prioritize economic considerations over demographic vulnerabilities, such as the well-being of children, the elderly, and individuals with disabilities or chronic illnesses.